PERAN PESANTREN DAN KELUARGA DALAM MEMBENTUK PERSEPSI KESETARAAN GENDER PADA SANTRI - Dewi, Lharasati; Anjani, Kusniatul; Nurainy, Niken Dwi; Husna, Haniatul; Fatimah, Gefira Nur (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2025)
The purpose of this study is to investigate how gender roles are formed within the family, which serves as a person's initial environment, and how pesantren, as a religious educational institution, can teach santri about gender equality. By offering suggestions to improve the collaboration between families and pesantren in fostering more inclusive and gender-equitable santri, this study also aims to evaluate how families and pesantren interact to promote awareness of gender justice and equality. The method used is qualitative, employing a literature review approach with sources such as books, journal articles, and research reports accessed through scientific databases. In addition to families, Islamic boarding schools hold a significant responsibility in educating a generation that is not only religiously knowledgeable but also socially conscious, particularly about gender equality. For example, at Pondok Pesantren Al-Husna Samarinda, female santri from class 2 MTs participated in learning activities that strengthened their understanding of gender justice. This pesantren provides equal opportunities for all students, regardless of gender, fostering an inclusive learning atmosphere where students are encouraged to reach their full potential and understand their rights and responsibilities without being constrained by gender preconceptions. By instilling values such as the equitable division of responsibilities in daily activities, Al-Husna plays a key role in challenging traditional views that still influence gender roles in Indonesia. Through its integrated religious and general curricula, supported by family engagement, pesantren like Al-Husna can promote gender justice and equality, helping to prevent stereotypes, foster diversity, and nurture a generation that values equality.